Revisiting the Hypothesis of High Discounts and High Unemployment - Paolo Martellini; Guido Menzio; Ludo Visschers (Institute of Labor Economics (IZA), 2019)
We revisit the hypothesis that labor market fluctuations are driven by shocks to the discount rate. Using a model in which the UE and the EU rates are endogenous, we show that an increase in the discount rate leads to a decline in both the UE and the EU rates. In the data, though, the UE and EU rates move against each other at business cycle frequency. Using a lifecycle model with human capital accumulation on the job, we show that an increase in the discount rate does indeed lead to a decline in the aggregate UE rate and to an increase in the aggregate EU rate. However, the decline in the UE rate is larger for younger workers than for older workers and the EU rate increases only for younger workers. In the data, fluctuations in the UE and EU rates at the business cycle frequency are nearly identical across age groups.
Keywords: E24; J63; J64; 330; unemployment fluctuations; discount rate; human capital; lifecycle earnings